Pathogenicity of meloidogyne javanica on the growth of lentil - Sharma, Ravi Datt; Gomes, Antônio Carlos (Pesquisa Agropecuaria Brasileira, 1992)
The pathogenicity of two populations of Meloidogyne javanica at five initial inoculum levels, i.e., 0, 10, 100, 1.000 and 10.000 eggs/kg of soil/plant of lentil (Lens culinaris Moench cv. CNPH - 237) was evaluated in greenhouse. The two populations of M. javanica were collected from bean (P1) and wheat (P2) cultivated at Planaltina, Brasília, Brazil, DF, in 1977. Population P2 had more effect on plant growth and number of bacterial nodules than P1 population. The nematodes multiplied at all the inoculum levels after 47 days. The multiplication rate of initial populations was much higher for P2 than in P1. Population P2 was more pathogenic to lentil than population P1. Lentil plant growth was stimulated with the inoculation of 0,1 egg/cm3 of soil for both populations (P1, P2) in relation to the control. Inoculum level of 10 egg/cm3 of soil and above for both populations (P1, P2) caused more damage to the growth of lentil.